The miracle of life [videorecording] - Nilsson, Lennart; WGBH (Television station : Boston, Mass.). (New York, N.Y. Crown Video, 1986)
A documentary which shows the actual conception and development of a baby. Looks inside the male and female reproductive organs to show the formation of sperm and the passage of a fertilized egg through the fallopian tube. Uses a microscope to observe DNA, chromosomes, and other minute body details building up to the moment of birth.
Title animation generated at the New York Institute of Technology.
VHS.
Photographed by Lennart Nilsson ; producers and directors, Bo G. Erikson and Carl O. Lofman.
Keywords: Human reproduction; Embryology, Human